As metamorfoses do eu e do texto: o jogo ficcional nos Tristia de Ovídio - Julia Batista Castilho de Avellar (2015)
This study focuses on the fictional game in Ovid's 'Tristia' ('Sadnesses'), collection of elegies which founded the exile poetry in the Western tradition, and its manifestation in the areas of first-person speaker and of text itself, in order to question the purely biographical readings that tended to stigmatize and decrease the literary value of the work. At the end, we present an annotated translation of the 'Tristia''s elegies that compose the analytical corpus. The first chapter discusses the various personae assumed by Naso, the exiled first-person speaker, who metamorphoses into barbarian, failed poet, epic anti-hero and mythographer. The second chapter, based on the analysis of meta-poetic passages, shows that the text proves to be multiple, wavering between truth and fiction: sometimes the information is presented as biographical and true, sometimes as literary fiction or jokes. Finally, the third chapter explains that this fictional game of alternations permeated by irony culminates in the metamorphosis of the exiled first-person speaker in his own book, which, rather than any other mask, is another poetic 'I'. The exiled Naso transfers the poetic voice to his book and, transformed into his own work, remains alive today thanks to literature